TEACHING WRITING DESCRIPTIVE TEXT THROUGH PICTURE WORD INDUCTIVE MODEL TO THE EIGHTH GRADE STUDENTS OF SMP MULIA PRATAMA - Berutu, Arie Sartika; Sembiring, Novalina; Pangaribuan, Jontra Jusat (Kairos English Language Teaching Journal, 2020)
Writing is an activity to share information in written form by combining some words into sentences and into paragraphs. Many students are still confused how to write a text because they do not know the rules and they can not express their ideas into written form. One of the strategies to teach writing is Picture Word Inductive Model (PWIM) whose its main activity is identifying and labelling all object and activities on the pictures. The method that is used in this research is Classroom Action Research (CAR). The subjects of this research are 25 students of Class VIII-4 of Junior High School Mulia Pratama Medan in the Academic Year of 2017/2018. Test, observation sheets, field note and questionnaire were used as the instruments for collecting the data. The result of this study showed increasing score of the students’ writing descriptive text. The result of the test showed that the students’ mean score in pre-test is 35,6 with 0% of the students got score ≥ 75, in formative test the mean score is 58,2 with 8% of the students got score ≥ 75 and in post-test the mean score is 69,5 with 24% of students got score ≥ 75. It showed that the percentage improvement of the students’ mean score from pre-test to post-test was 24%. The responses of students after being taught by using Picture Word Inductive Model are good. The students enjoyed the process of teaching and learning. It is suggested that teachers use Picture Word Inductive Model in teaching writing skill to improve the students’ skill in writing descriptive texts.